A sulfur‐based transport pathway in Cu+‐ATPases. (8th May 2015) - Mattle, Daniel; Zhang, Limei; Sitsel, Oleg; Pedersen, Lotte Thue; Moncelli, Maria Rosa; Tadini‐Buoninsegni, Francesco; Gourdon, Pontus; Rees, Douglas C; Nissen, Poul; Meloni, Gabriele
Abstract Cells regulate copper levels tightly to balance the biogenesis and integrity of copper centers in vital enzymes against toxic levels of copper. PIB‐type Cu+‐ATPases play a central role in copper homeostasis by catalyzing the selective translocation of Cu+ across cellular membranes. Crystal structures of a copper‐free Cu+‐ATPase are available, but the mechanism of Cu+ recognition, binding, and translocation remains elusive. Through X‐ray absorption spectroscopy, ATPase activity assays, and charge transfer measurements on solid‐supported membranes using wild‐type and mutant forms of the Legionella pneumophila Cu+‐ATPase (LpCopA), we identify a sulfur‐lined metal transport pathway. Structural analysis indicates that Cu+ is bound at a high‐affinity transmembrane‐binding site in a trigonal‐planar coordination with the Cys residues of the conserved CPC motif of transmembrane segment 4 (C382 and C384) and the conserved Met residue of transmembrane segment 6 (M717 of the MXXXS motif). These residues are also essential for transport. Additionally, the studies indicate essential roles of other conserved intramembranous polar residues in facilitating copper binding to the high‐affinity site and subsequent release through the exit pathway.